2019
DOI: 10.3390/jcm8071051
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effects of Day-Time vs. Night-Time Surgery on Renal Transplant Patient Outcomes

Abstract: Sleep deprivation and disruption of the circadian rhythms could impair individual surgical performance and decision making. For this purpose, this study identified potential confounding factors on surgical renal transplant patient outcomes during day and night. Our retrospective cohort study of 215 adult renal cadaver transplant recipients, of which 132 recipients were allocated in the “day-time” group and 83 recipients in the “night-time” group, primarily stratified the patients into two cohorts, depending on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…3 | RESULTS (Table 1). Patients in the evening cohort were more likely to be transferred from outside centers (75% vs. 70.8%; p = .003), had shorter times from presentation to procedure (6 h [4][5][6][7][8][9][10][11][12] vs. 7 h [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]; p = .004), and fewer known aortic aneurysms (12.1% vs. 15.0%; p = 0.011), previous dissections (3.4% vs. 4.8%; p = .040), and prior cardiac operations (9.5% vs.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…3 | RESULTS (Table 1). Patients in the evening cohort were more likely to be transferred from outside centers (75% vs. 70.8%; p = .003), had shorter times from presentation to procedure (6 h [4][5][6][7][8][9][10][11][12] vs. 7 h [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]; p = .004), and fewer known aortic aneurysms (12.1% vs. 15.0%; p = 0.011), previous dissections (3.4% vs. 4.8%; p = .040), and prior cardiac operations (9.5% vs.…”
Section: Study Populationmentioning
confidence: 99%
“…[1][2][3][4] However, findings of increased surgical morbidity and mortality during evening hours are by no means universal, as some data show no difference in outcomes for surgical procedures during evening hours. [5][6][7][8][9] The relevance to the public health community for maintaining patient safety during surgery, despite evening operative hours, cannot be overstated. It was estimated by the Institute of Medicine that in any given year, 98,000 patients die as a results of hospital errors made by staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 33 ] In addition, in a paper [ 34 ] that surveyed 27,305 cardiac surgery patients between 2010 and 2017 to compare morning and afternoon cardiac surgeries (procedures that included coronary artery bypass graft with internal mammary, or thoracic artery and vein or radial artery bypass) in regard to surgical site infections and mortality, the conclusion was that current evidence is not enough to favor afternoon cardiac surgeries, and that increased rates of morning myocardial infarction were not associated with an impact on the 1-year deep surgical site infections or mortality rate. Furthermore, there are a number of studies [ 35 37 ] of different transplant surgical procedures that have concluded that there is no higher risk, no poorer outcomes, and no adverse complications during nighttime surgeries compared to daytime.…”
Section: Discussionmentioning
confidence: 99%
“…For example, operative timing in emergency general surgery was associated with increased postoperative complications (14) and the operative start time of cardiac surgery affected i n t r a o p e r a t i v e t r a n s f u s i o n r a t e s ( 1 5 ) . H o w e v e r, postoperative complications and overall survival rates did not vary with start time in the performance of radical gastrectomy (16), hip fracture fixation (17), renal transplantation (18), and liver resection (19). The outcome of minimal invasive endometrial cancer surgery and laparoscopic sacrocolpopexy (20) also had no association with operative start time (21) and although afternoon surgeries were found to be associated with increased levels of cortisol and inflammatory cytokines [interleukin (IL)-6, IL-8] (22), no conclusion of correlation between operation time and postoperative infectious complications (23).…”
Section: Introductionmentioning
confidence: 96%